Octomeria giordanii (Orchidaceae—Pleurothallidinae), a new species from Brazil and nomenclatural notes on João Barbosa Rodrigues’s species that occurs in Bahia and Minas Gerais - Santos, Thiago Faria Dos; Menezes, Euler Da Luz Fernandes (Phytotaxa, 2023)
Octomeria giordanii is proposed as a new species occurring in an ecotone between the Atlantic Rainforest and Cerrado biomes in Minas Gerais, Brazil. This study provides a detailed description, illustrations, and a comparative analysis using an identification key to distinguish it from other Octomeria species. The new species is characterized by its small size, rupicolous reptant growth habit, and flowers with multiple colors. It shares similarities with O. fusiformis and other Octomeria species but can be differentiated by its floral morphology and ecology. The nomenclatural notes include the lectotypification of nine taxa described by João Barbosa Rodrigues that can be found occurring in the states of Bahia and Minas Gerais. Additionally, O. albiflora is proposed as a new synonym of O. lithophila.